2001
DOI: 10.1176/appi.ps.52.7.943
|View full text |Cite
|
Sign up to set email alerts
|

Benefits in Behavioral Health Carve-Out Plans of Fortune 500 Firms

Abstract: The carve-out contracts of the Fortune 500 firms in this study typically covered a wide range of services, and the benefits appeared generous relative to those reported for other integrated and carve-out plans. However, these benefits generally did not reach the level of parity with typical medical benefits, nor did they fully protect enrollees from the risk of catastrophic expenditures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…For mental health, these findings corroborate earlier work on cost sharing in employer plans (Salkever, Shinogle, and Goldman 1999;Sturm and McCulloch 1998;Merrick et al 2001). For substance abuse treatment, these results are new, given the lack of prior data.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…For mental health, these findings corroborate earlier work on cost sharing in employer plans (Salkever, Shinogle, and Goldman 1999;Sturm and McCulloch 1998;Merrick et al 2001). For substance abuse treatment, these results are new, given the lack of prior data.…”
Section: Discussionsupporting
confidence: 82%
“…Two exceptions are Peele, Lave, and Xu (1999), who report that substance abuse cost sharing was the same as for mental health in all but 1 of 46 plans with a single MBHO, and Merrick et al (2001), who found that cost sharing was the same for 94 percent of large employers who carved out behavioral health.…”
Section: Prior Studiesmentioning
confidence: 99%
“…Performance standards to monitor staffing ratios have not been widely adopted by employers in their contracts with carve outs rendering behavioral care. 26 The situation in public sector managed mental health care appears at best to be analogous. A recent nationwide study of Medicaid managed-care contracts reports that states are making efforts to specify standards regarding network structure to promote access to general medical care, but these were found to be missing or very general in the case of specialty care.…”
Section: Implications For Behavioral Health Servicesmentioning
confidence: 99%
“…For example, of the 336 Fortune 500 companies surveyed by Elizabeth Merrick and colleagues, 39 percent reported firm-level contracts with MBHOs. 13 This study did not examine employees with carved-out benefits at the plan level.…”
Section: Study Findingsmentioning
confidence: 99%